Comparison of postoperative analgesia with two different doses of dexmedetomidine as an adjuvant to ropivacaine in adductor canal block for unilateral total knee replacement surgery: A randomized double-blinded study - Naveen M Karthik; S Gokul Das; Jasmin Johney; Mathew George; Eldo Issac; Anu Vasudevan (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Multimodal analgesia is used to treat severe postoperative pain (POP) in total knee replacement (TKR) surgery. Adjuvants are used with local anesthetics to improve the quality and duration of pain relief. Studies comparing different doses of dexmedetomidine in adductor canal block (ACB) are sparse to date. This study compares postoperative analgesia with two different doses of dexmedetomidine as an adjuvant to 0.2% ropivacaine in ACB for unilateral TKR. Material and Methods: In this prospective, randomized, double-blinded comparative study, sixty patients were divided into two groups: A and B. Postoperatively perineural catheter was inserted and all patients received 0.2% ropivacaine 20 mL bolus followed by an infusion of 0.2% ropivacaine with dexmedetomidine (0.5 μg/Kg in Group A and 1 μg/Kg in Group B) at 8 mL/h. Postoperative pain, motor blockade, rescue analgesia, hemodynamic parameters, sedation, and adverse effects were recorded. Student t, Chi-square, and Mann-Whitney tests were used. Results: Most patients were elderly females (M:15, F:45). Postoperatively, from 2nd to 24th hour, pain score was less in Group B (P < 0.05). The requirement of rescue analgesic was also less in Group B (A:B 330 μg:60 μg; 23%:6%). Motor blockade assessed using modified Bromage scale and sedation using Richmond agitation sedation scale did not show any statistical difference. Conclusion: Dexmedetomidine infusion at 1 μg/Kg is a better adjuvant to 0.2% ropivacaine than 0.5 μg/Kg in ACB. It provides better analgesia without producing sedation, motor blockade, hemodynamic changes, or any adverse effects.